Alms-Awareness Behavior, Serotonin Hormone, And Corporate Age - La Ode Sumail; Hasbiyadi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
Humans who are fragmented in their souls or (split personality) are easily infested with mental poisons, so we need detolks in the form of alms. We investigate the influence of religiosity, attitudes and subjective norms on alms awareness and impact on corporate age through the role of the hormone serotonin. Because the characteristics of PT Haji La Tunrung's ownership are family ownership and are currently directed by second generation family members, it is interesting to be chosen as the object of research. We believe that owners, managers and employees can provide accurate and quality information (purposive sampling) and analyze data using WarpPLS 7.0. We find that the better religiosity, attitudes and subjective norms the higher the awareness of charity and the age of corporations increases. Sadaqah awareness can increase the hormone serotonin. Therefore, the hormone serotonin can increase self-confidence for individuals and corporations and performance is good so that the age of corporations increases. We also find that higher levels of formal education are not the only determinant of alms awareness.